Designing Multimodal Teaching Materials Using The Addie Model for University Students - Paramita, Paulina Erawati (Indo Publishing, 2026)
This article discusses the presentation of the concept of designing multimodal teaching materials using the ADDIE model, delivered online via the Zoom platform at the ASES X. International Social Sciences Congress. This activity was motivated by the need to share insights on educational innovation in higher education, particularly in designing teaching materials that are responsive to the needs of digital-native students. The purpose of this presentation was to introduce the ADDIE framework as a systematic solution for developing multimodal teaching materials and to gain feedback from international academics. The method used was an oral presentation conducted virtually, followed by a Q&A session and interactive discussion with congress participants. The result achieved was the effective dissemination of ideas, marked by in-depth discussions and high participant enthusiasm, despite being conducted online. The feedback received indicated that the ADDIE model is perceived as relevant and applicable in diverse educational contexts. In conclusion, online-based international scientific forums like the ASES Congress prove to be effective venues for disseminating educational innovation and exchanging ideas among academics across countries.